Pengaruh Brand Image, Lokasi, dan Harga terhadap Minat Beli Pelanggan pada Toko Thrifting di USD Bundle Kediri - Restu Ade Nugraha; Anita Anita; Nuril Aulia (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to examine the influence of brand image, location, and price on customers’ purchase intention at the USD Bundle thrifting store in Kediri. This research employed a quantitative approach using purposive sampling, involving 152 respondents who were active customers of USD Bundle. Data were analyzed through classical assumption tests, multiple linear regression, t-test, and F-test using SPSS 25. The results indicate that brand image, location, and price each have a positive and significant effect on purchase intention. Simultaneously, these variables also show a positive and significant impact, with a coefficient of determination (R²) of 0.954, meaning that 95.4% of the variation in purchase intention is explained by brand image, location, and price. These findings highlight that a strong brand image, strategic location, and competitive pricing play essential roles in increasing customer purchase intention in thrifting businesses, particularly within urban environments such as Kediri City.